(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The appreciation of the constitutionality of homeschooling (homeschooling) by the Federal Supreme Court in Extraordinary Appeal 888.815/RS standardized national jurisprudence by declaring said constitutional method. The decision, however, removed the dialogic stance with the Legislature to resolve the normative omission on the subject that makes the practice of homeschooling in Brazil illegal. The critical jurisprudential analysis will allow to point out some impacts of the court decision that has had repercussions on the legislative omission on the subject.